2007
DOI: 10.1128/jvi.00255-07
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Rodent Herpesviruses, Including the First Gammaherpesvirus of Mus musculus

Abstract: Rodent herpesviruses such as murine cytomegalovirus (host, Mus musculus), rat cytomegalovirus (host, Rattus norvegicus), and murine gammaherpesvirus 68 (hosts, Apodemus species) are important tools for the experimental study of human herpesvirus diseases. However, alphaherpesviruses, roseoloviruses, and lymphocryptoviruses, as well as rhadinoviruses, that naturally infect Mus musculus (house mouse) and other Old World mice are unknown. To identify hitherto-unknown rodent-associated herpesviruses, we captured M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(112 citation statements)
references
References 27 publications
(21 reference statements)
3
105
2
Order By: Relevance
“…As airlifts to Afghanistan were conducted from both areas (Cologne airport and Leipzig airport), animals from Western Germany and North Western Czech Republic (representing the Central European M. m. musculus population) were selected. The trapping of control animals for astrovirus and herpesvirus investigations at five sites in Germany and one site in the United Kingdom have been reported previously [13,17,18]. As no morphological vouchers could be preserved in this study, some preliminary species identifications were based on the photographic documentation and comparisons with museum specimens.…”
Section: Small Mammal Trapping and Transfer Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…As airlifts to Afghanistan were conducted from both areas (Cologne airport and Leipzig airport), animals from Western Germany and North Western Czech Republic (representing the Central European M. m. musculus population) were selected. The trapping of control animals for astrovirus and herpesvirus investigations at five sites in Germany and one site in the United Kingdom have been reported previously [13,17,18]. As no morphological vouchers could be preserved in this study, some preliminary species identifications were based on the photographic documentation and comparisons with museum specimens.…”
Section: Small Mammal Trapping and Transfer Proceduresmentioning
confidence: 99%
“…PCR amplification of the cytochrome b gene was conducted for each sample as described above to determine DNA amplificability. Amplification of the DPOL gene was conducted as described before [17]. Briefly, PCR was performed in nested format using a mixture of six degenerated/deoxyinosine substituted primers and delivering an expected Resulting PCR products were subjected to gel electrophoresis in a 3% agarose gel in 1× TAE buffer at 100 V for 45 min.…”
Section: Sequence Determination and Analysis Of The Mitochondrial D-loopmentioning
confidence: 99%
See 1 more Smart Citation
“…Deletion mutant VZV virus infection of skin and T cells xenografts in vivo also indicated that ORF35 is a determinant of VZV virulence (Ito et al, 2005). It would be important to analyze the ORF20 mutant MHV-68 pathogenesis in its natural host, the wood mice (members of the genus Apodemus) (Ehlers et al, 2007), as a recent comparative analysis revealed that MHV-68 infection of BALB/c (M. musculus) and laboratory-bred wood mice are markedly different (Hughes et al, 2010). In conclusion, manipulation of the DNA damage response is a major target of herpesviruses, and one that in turn may determine a variety of significant outcomes to favor the virus, with cell cycle arrest and induction of IL-8 now identified.…”
Section: The Ul24 Family: Multifunctional Virus Host Evasion Proteinsmentioning
confidence: 99%
“…Epidemiological surveys in the UK, Germany, France, and Peru found several other gammaherpesviruses in free-living rodents [3][4][5][6]. Although it has been documented that MHV-68 is mainly transmitted in the rodent population via intranasal routes and through body fluids, such as saliva, urine, tears, and breast milk, it is not yet fully understood how this virus spreads in nature.…”
Section: Introductionmentioning
confidence: 99%